PEMANFAATAN MEDIA MAGIC SPIN BOARD MELALUI MODEL DISCOVERY LEARNING UNTUK MENINGKATKAN LITERASI SAINS SISWA KELAS V SDN SENDANGAGUNG - Puspita Ayu Idhayana; Khamdun; Lintang Kironoratri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2023)
This study aims to determine the increase in scientific literacy by using the magic spin board media through the discovery learning model. The research method used was classroom action research with the subject of 20 fifth grade students at SD Negeri Sendangagung. The research was conducted in two cycles and each cycle consisted of two meetings held on the theme of 7 event in life. The research stages consist of planning, implementation, observation, and reflection. The results showed that the average percentage for cycle 1 was 68,41%, and for cycle 2 was 80,06% which showed an increase in each cycle. The result showed that there was an increase in scientific literacy of 11,65% by using the magic spin board media with the discovery learning.